MORFOMETRY OF GOATS (Capra aegagrus) IN RASAU JAYA III VILLAGE, RASAU JAYA DISTRICT KUBU RAYA DISTRICT, PROVINCE KALIMANTAN BARAT - Guntur, Muhammad; Tohardi, Ahmad; Rohayeti, Yeti (Jurnal Sains Mahasiswa Pertanian, 2020)
This study aims to determine the morphometry of the Goat Goat which is maintained intensively in Rasau Jaya III Village, Rasau Jaya District, Kubu Raya Regency, West Kalimantan Province. The variables observed were chest circumference, chest width, chest depth, shoulder height, hip height, body length and body weight. The results showed that adult male breast circumference was 74.53 ± 6.99 cm and adult female was 72.36 ± 6.43 cm. adult male chest width 20.93 ± 4.54 cm and adult female 19.71 ± 6.94 cm, in adult male chest 30.73 ± 3.67 cm and adult female 28.93 ± 6.17 cm, shoulder height adult males 60.47 ± 3.70 cm and adult females 66.43 ± 5.37 cm, adult male hip height 63.33 ± 4.02 cm and adult females 64.79 ± 6.61 cm, adult male body length 67 , 27 ± 5.28 cm and adult female 76.07 ± 6.73 cm, adult male body weight 30.06 ± 4.50 kg and adult female 27.8 ± 10.0 kg. Based on the results of the morphometry research of Kacang Goat in Rasau Jaya III Village is higher than the Decree of the Minister of Agriculture, 2012. Keywords: Goat Nut, chest circumference, chest width, chest height, shoulder height, hip height, body length and body weight